High Complexity Assisted Reproduction Treatments In The Reproductive Medicine Service At The Maternal Perinatal National Institute Experience August-November 2014 - Garnique-Moncada, Marco (2017)
Objectives. To describe and evaluate the outcome of highly complex assisted reproduction treatments in the Reproductive MedicineService of the INMP in the period August-November 2014. Material and methods. Descriptive, observational and retrospectivestudy. We included all patients with indications of highly complex assisted reproduction treatments who received at least one InVitro Fertilization cycle during August-November 2014. Each patient received a cycle of ovarian stimulation with recombinantfollicle stimulating hormone (FSH-r) and / Or Highly Purified Human Menopause Hormone (HMG-HP), Cetrorelix and ChorionicGonadotropin (HCG) Hormone. All patients received a regimen of controlled ovarian stimulation, follicular aspiration, In VitroFertilization and Embryo Transfer in the Reproductive Medicine Service and Laboratory of Gametes and Embryos of the INMP. Day3 embryos (stage D + 3) were transferred. Clinical records were reviewed with a collection record and the data obtained were sortedand processed in a database using the SPSS Version 19 statistical package.